Viral load suppression in HIV-infected adolescents in cameroon: towards achieving the UNAIDS 95% viral suppression target - Armando B. D. Djiyou; Calixte Ida Penda; Yoann Madec; Grace Dalle Ngondi; Astrid Moukoko; Marie Varloteaux; Laure-Amélie de Monteynard; Cecile Moins; Carole Else Eboumbou Moukoko; Avelin F. Aghokeng (BMC, 2023)
Abstract Background Achieving the UNAIDS 95% sustained viral suppression (VS) rate requires considerable global efforts, particularly among adolescents living with HIV (ALHIV) who are often associated with high rates of virological failure (VF). In this study, we prospectively assessed the rate of VS, and the factors associated with VF in a cohort of adolescents followed up according to the WHO guidelines in Cameroon. Methods A cross-sectional study was carried out in 2021 among adolescents (aged 10-19 years) receiving ART in the national program in Cameroon. Socio-demographic and clinical data were collected using patients' medical files and a brief interview with the participant and/or his guardian. Thereafter, a first viral load test (VL1) was performed using the ABBOTT Platform. For adolescents with VL1 > 1000 copies/ml, adherence-enhancing interventions were routinely performed each month for 3 consecutive months, after which a second viral load (VL2) was measured. Adolescents with VL2 > 1000 copies/ml were considered in VF. Results Overall, 280 adolescents were enrolled, of whom 89.3% (250/280) acquired HIV infection via mother-to-child transmission. The median age was 16.0 (IQR: 13.0-18.0) years and the median duration on ART was 9.8 (IQR: 5.1-12.8) years. Females and males were almost equally represented, as 52.1% (146/280) were female, while 47.9% (134/280) were males (p = 0.47). The VS rate was 88.2% (CI: 83.8-91.7%) overall; 89.0% (CI: 82.0-93.1%) and 88.7% (CI: 81.2-93.0%) in females and males, respectively. Being on second or third-line ART, self-declared suboptimal adherence, and a history of past VF were independently associated with VF. Conclusion The high rate of VS we report in this study is welcome in the era of the 95/95/95 UNAIDS goals, and indicates that improving treatment outcomes in this specific and fragile population that represent adolescents in Sub-Saharan Africa is achievable. Trial registration 20/10/2020 NCT04593979 ( https://clinicaltrials.gov/ct2/show/NCT04593979 ).